The first record of the bark louse genus Symbiopsocus (Psocodea: Psocidae) from Vietnam, with description of a new species - Ning, Jinjin; Li, Fasheng; Liu, Xingyue (Zootaxa, 2020)
The bark louse genus Symbiopsocus includes 23 species, all of which known from East Asia. Here we report the first record of Symbiopsocus from Vietnam, with description of Symbiopsocus vietnamicus sp. nov. A revised key to the species of Symbiopsocus is provided.